METHODICAL APPROACH TO COMPLEX ASSESSMENT OF QUALITY OF CUSTOMS SERVICES - Yu. Gupanova; Yu. Chechulin (Вестник университета)
Based on a critical analysis of existing scientific papers in the field of assessing the quality of customs services and the activities of customs authorities as a whole, the need to develop a methodological approach to a comprehensive assessment of the quality of customs services has been revealed and substantiated. At the same time, an author’s approach to an integrated assessment of the quality of customs services has been proposed, which includes the principles of assessment, assessment directions, the method for calculating the overall integral quality assessment and specific indicators, which can be used to evaluate each of the directions.